2015
DOI: 10.3892/etm.2015.2240
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves the paclitaxel-induced apoptosis of HPV-positive human cervical cancer cells via the NF-κB-p53-caspase-3 pathway

Abstract: Paclitaxel, isolated from Taxus brevifolia, is considered to be an efficacious agent against a wide spectrum of human cancers, including human cervical cancer. However, dose-limiting toxicity and high cost limit its clinical application. Curcumin, a nontoxic food additive, has been reported to improve paclitaxel chemotherapy in mouse models of cervical cancer. However, the underlying mechanisms remain unclear. In this study, two human cervical cancer cell lines, CaSki [human papilloma virus (HPV)16-positive] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 51 publications
(65 reference statements)
2
42
0
Order By: Relevance
“…Several studies have shown curcumin to be a promising sensitizer to chemotherapeutic agents, including paclitaxel, in a wide variety of tumor cell types (Kumar et al, 2017; Zhang et al, 2017; Zou et al, 2018; Dang et al, 2015; Lu et al, 2017; Zhan et al, 2014). Curcumin combined with standard docetaxel chemotherapy led to a significant improvement and clinical response in patients with metastatic breast cancer in a phase I clinical trial (Bayet-Robert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown curcumin to be a promising sensitizer to chemotherapeutic agents, including paclitaxel, in a wide variety of tumor cell types (Kumar et al, 2017; Zhang et al, 2017; Zou et al, 2018; Dang et al, 2015; Lu et al, 2017; Zhan et al, 2014). Curcumin combined with standard docetaxel chemotherapy led to a significant improvement and clinical response in patients with metastatic breast cancer in a phase I clinical trial (Bayet-Robert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin combined with standard docetaxel chemotherapy led to a significant improvement and clinical response in patients with metastatic breast cancer in a phase I clinical trial (Bayet-Robert et al, 2010). Considering the pleiotropic activity of curcumin in cancer prevention, it could be involved in chemosensitization in several different ways, such as inhibition of NF-κB signaling (Dang et al, 2015), miRNA-induced suppression of cell proliferation (Lu et al, 2017), and modulation of epidermal growth factor receptor (EGFR) signaling (Zhan et al, 2014). Our results showed that Lin28B expression in Hep3B/TAX cells and xenograft tumor tissue was significantly decreased in a dose-dependent manner following co-treatment with curcumin and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…These antineoplastic and apoptotic effects were enhanced when diclofenac and curcumin were administered together, rather than individually [7 && ]. In a recently published paper [8], curcumin demonstrated the ability to improve the paclitaxel-induced apoptosis of human papillomavirus (HPV) positive human cervical cancer cell lines via the nuclear factor (NF)-kB-p53-caspase-3 pathway. The study concluded that curcumin combined with paclitaxel may provide superior therapeutic effects on human cervical cancer.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Curcumin has been reported to synergistically enhance the cell growth inhibitory activity of Paclitaxel, a chemotherapeutic, in HPV‐positive human cancer cell lines, as it increased E6/E7 protein inhibition and thereby restored cellular p53 and pRb levels . Using a raft culture technique in which the multilayered and differentiated cell growth of epithelial cells supported the development of HPV in vitro , curcumin alone was able to induce cell death in HPV16 infected CaSki cells and the cleavage products of caspase 9 and 3 (indicators of apoptosis) were found .…”
Section: Anti‐hpv and Anticancer Effects Of Curcumin: Molecular Mechamentioning
confidence: 99%
“…These are just some of the mechanisms elucidated to date as to why therapeutic interventions, while harmful to cancer cells, have failed in achieving an absolute treatment success . Therefore, adjuvant agents that can offer specific cancer toxicity or synergistic effects along with the current nonspecific, noxious chemo‐agents, are desperately needed .…”
Section: Introductionmentioning
confidence: 99%